(3aVGFd TgQ QeVGfs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3bGd MOKfG CHj QMeg Gddg Yf eMeO Hf jMji GdYWGQ Yf CMeO Hf eMeO Hf YjSi Yf GdMSf Hf eMHhH Yf CHj CjhH Yf CHj GdhQOYj (B...s
(3BNQgG (B:s
... (3Yf CHj gQjQI bGd bGd QShd Gddg Udi Gddg Ydjg hBdg (B" (3QH UGFe MXg ef UjGeg GdLhY hQH bGFe MXg ef bjGe GdSgQ(B.s
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfj Yf fSNI Yf fSNI Yf fSNI HNW GdeUfas
(3JHUQI GdYfhGf (B:s
(3Ydi WQI GdQSGdI HNW GdeUfa (B: (3PcQ GdeUfa gPG GdcJGH aj BNQ HGH KhGH Uhe QeVGf aj cJGHg eG dG jMVQg Gdabjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \274s
(3GdPQjYI (B16 - 178 ( 1012 )s
Keywords: (3GdMOjK hGdeUWdMs